Campylobacter jejuni bile exposure influences outer membrane vesicles protein content and bacterial interaction with epithelial cells. Issue 1 (December 2018) - Taheri, Nayyer; Mahmud, A.; Sandblad, Linda; Fällman, Maria; Wai, Sun; Fahlgren, Anna
Abstract Campylobacter jejuni is a prevalent human pathogen and a major cause of bacterial gastroenteritis in the world. In humans, C .jejuni colonizes the intestinal tract and its tolerance to bile is crucial for bacteria to survive and establish infection.C .jejuni produces outer membrane vesicles (OMVs) which have been suggested to be involved in virulence. In this study, the proteome composition ofC .jejuni OMVs in response to low concentration of bile was investigated. We showed that exposure ofC .jejuni to low concentrations of bile, similar to the concentration in cecum, induced significant changes in the protein profile of OMVs released during growth without affecting the protein profile of the bacteria. This suggests that bile influences a selective packing of the OMVs after bacterial exposure to low bile. A low concentration of bile was found to increase bacterial adhesion to intestinal epithelial cells, likely by an enhanced hydrophobicity of the cell membrane following exposure to bile. The increased bacterial adhesiveness was not associated with increased invasion, instead bile exposure decreasedC .jejuni invasion. OMVs released from bacteria upon exposure to low bile showed to increase both adhesion and invasion of non-bile-exposed bacteria into intestinal epithelial cells. These findings suggest thatC .jejuni in environments with low concentrations of bile produce OMVs that facilitates colonization of the bacteria, and this could potentially contribute to virulence ofC .jejuni in the gut.